Integration of post-communist countries in the EU: Leaders and losers? - Lukáš Cíbik; Peter Horváth; Richard Brix (Comparative Economic Research. Central and Eastern Europe, 2022)
The economic indicators of the new member states of the EU that joined after 2004 have been generally positive. In this paper, we analyse and interpret the economic development results of the 11 new Member States from the Eastern bloc. The set of individual economic indicators gives us a relatively realistic picture of the differences in development in individual post-communist countries. The paper points out several factors which, in principle, create two groups of countries for us in terms of the development of economic indicators: A more progressive group of countries, which for the most part is showing progress towards catching up with the EU average, and a less progressive group, whose pace of convergence is significantly slower.
Keywords: E6; E62; F02; F62; 330; economic; development; the difference; post-communist countries; EU